Induction chemotherapy with lobaplatin and fluorouracil versus cisplatin and fluorouracil followed by chemoradiotherapy in patients with stage III–IVB nasopharyngeal carcinoma: an open-label, non-inferiority, randomised, controlled, phase 3 trial. Issue 5 (May 2021) - Lv, Xing; Cao, Xun; Xia, Wei-Xiong; Liu, Kui-Yuan; Qiang, Meng-Yun; Guo, Ling; Qian, Chao-Nan; Cao, Ka-Jia; Mo, Hao-Yuan; Li, Xian-Ming; Li, Zi-Huang; Han, Fei; et al.
Summary: Background: Cisplatin-based induction chemotherapy plus concurrent chemoradiotherapy in the treatment of patients with locoregionally advanced nasopharyngeal carcinoma has been recommended in the National Comprehensive Cancer Network Guidelines. However, cisplatin is associated with poor patient compliance and has notable side-effects. Lobaplatin, a third-generation platinum drug, has shown promising antitumour activity against several malignancies with less toxicity. In this study, we aimed to evaluate the efficacy of lobaplatin-based induction chemotherapy plus concurrent chemoradiotherapy over a cisplatin-based regimen in patients with locoregional, advanced nasopharyngeal carcinoma. Methods: In this open-label, non-inferiority, randomised, controlled, phase 3 trial done at five hospitals in China, patients aged 18–60 years with previously untreated, non-keratinising stage III–IVB nasopharyngeal carcinoma; Karnofsky performance-status score of at least 70; and adequate haematological, renal, and hepatic function were randomly assigned (1:1) to receive intravenously either lobaplatin-based (lobaplatin 30 mg/m 2 on days 1 and 22, and fluorouracil 800 mg/m 2 on days 1–5 and 22–26 for two cycles) or cisplatin-based (cisplatin 100 mg/m 2 on days 1 and 22, and fluorouracil 800 mg/m 2 on days 1–5 and 22–26 for two cycles) induction chemotherapy, followed by concurrent lobaplatin-based (two cycles of intravenous lobaplatin 30 mg/m 2 every 3 weeks plus intensity-modulated radiotherapy) or cisplatin-based (two cycles of intravenous cisplatin 100 mg/m 2 every 3 weeks plus intensity-modulated radiotherapy) chemoradiotherapy. Total radiation doses of 68–70 Gy (for the sum of the volumes of the primary tumour and enlarged retropharyngeal nodes), 62–68 Gy (for the volume of clinically involved gross cervical lymph nodes), 60 Gy (for the high-risk target volume), and 54 Gy (for the low-risk target volume), were administered in 30–32 fractions, 5 days per week. Randomisation was done centrally at the clinical trial centre of Sun Yat-sen University Cancer Centre by means of computer-generated random number allocation with a block design (block size of four) stratified according to disease stage and treatment centre. Treatment assignment was known to both clinicians and patients. The primary endpoint was 5-year progression-free survival, analysed in both the intention-to-treat and per-protocol populations. If the upper limit of the 95% CI for the difference in 5-year progression-free survival between the lobaplatin-based and cisplatin-based groups did not exceed 10%, non-inferiority was met. Adverse events were analysed in all patients who received at least one cycle of induction chemotherapy. This trial is registered with the Chinese Clinical Trial Registry, ChiCTR-TRC-13003285 and is closed. Findings: From June 7, 2013, to June 16, 2015, 515 patients were assessed for eligibility and 502 patients were enrolled: 252 were randomly assigned to the lobaplatin-based group and 250 to the cisplatin-based group. After a median follow-up of 75·3 months (IQR 69·9–81·1) in the intention-to-treat population, 5-year progression-free survival was 75·0% (95% CI 69·7–80·3) in the lobaplatin-based group and 75·5% (70·0 to 81·0) in the cisplatin-based group (hazard ratio [HR] 0·98, 95% CI 0·69–1·39; log-rank p=0·92), with a difference of 0·5% (95% CI −7·1 to 8·1; pnon-inferiority =0·0070). In the per-protocol population, the 5-year progression-free survival was 74·8% (95% CI 69·3 to 80·3) in the lobaplatin-based group and 76·4% (70·9 to 81·9) in the cisplatin-based group (HR 1·04, 95% CI 0·73 to 1·49; log-rank p=0·83), with a difference of 1·6% (−6·1 to 9·3; pnon-inferiority =0·016). 63 (25%) of 252 patients in the lobaplatin-based group and 63 (25%) of 250 patients in the cisplatin-based group had a progression-free survival event in the intention-to-treat population; 62 (25%) of 246 patients in the lobaplatin-based group and 58 (25%) of 237 patients in the cisplatin-based group had a progression-free survival event in the per-protocol population. The most common grade 3–4 adverse events were mucositis (102 [41%] of 252 in the lobaplatin-based group vs 99 [40%] of 249 in the cisplatin-based group), leucopenia (39 [16%] vs 56 [23%]), and neutropenia (25 [10%] vs 59 [24%]). No treatment-related deaths were reported. Interpretation: Lobaplatin-based induction chemotherapy plus concurrent chemoradiotherapy resulted in non-inferior survival and fewer toxic effects than cisplatin-based therapy. The results of our trial indicate that lobaplatin-based induction chemotherapy plus concurrent chemoradiotherapy might be a promising alternative regimen to cisplatin-based treatment in patients with locoregional, advanced nasopharyngeal carcinoma. Funding: National Science and Technology Pillar Program, International Cooperation Project of Science and Technology Program of Guangdong Province, Planned Science and Technology Project of Guangdong Province, and Cultivation Foundation for the Junior Teachers at Sun Yat-sen University. Translation: For the Chinese translation of the abstract see Supplementary Materials section.